THE EFFECT OF USING THE ‘KLIK KB’ APPLICATION ON THE LEVEL OF KNOWLEDGE, ATTITUDES AND BEHAVIOR IN CHOOSING CONTRACEPTIVES AT PMB “R” - Nursifa, Niknik; Fatonah, Sofa (Ikatan Perawat Maternitas Indonesia Provinsi Jawa Barat, 2025)
Research on digital platforms for family planning was scarce, and many studies only measured knowledge without examining changes in attitudes or actual contraceptive-choice behavior. Comprehensive evaluations of the application before and after use were also lacking, leaving insufficient evidence of its effectiveness as an educational tool. This created a clear research gap, highlighting the need to examine the influence of the “KLIK KB” application on users’ knowledge, attitudes, and behaviors in choosing contraceptive methods. This study was to determine the increase in knowledge, attitudes and behaviors in women of childbearing age about contraceptive methods before and after using the Klik KB application. The design of this study was quantitative research that used a pre-experimental design with a one-group pretest–posttest type. This design did not have a comparison (control) group. The instruments used were questionnaires, all of which had been validated and reliability-tested beforehand. The population consisted of 30 respondents, and total sampling was used with accidental sampling to select all 30 respondents. This study used a paired sample t-test. The research was conducted in the Batu Jajar area of West Bandung Regency from May to August 2025. The result is an influence on the use of the Klik KB application on knowledge, attitudes and behavior in choosing contraceptives. There is an influence on the use of the Klik KB application on knowledge, attitudes and behavior in choosing contraceptives. Suggestions for future researchers were advised to use a larger sample for stronger results. Keywords: Attitude, behavior, klik KB application, knowledge, women of childbearing, age.